The classroom in times of COVID-19: The outcome of remote classes in elementary school I - Jesus , Gilda Oliveira de; Marinho , Valdemiro Lopes (Seven Editora, 2023)
Technological advancement has long been leaving its mark and demarcating its territory around the world, giving rise to new models, perspectives, new means of communication and a new vision of teaching and learning. However, despite all this digital advancement, the educational network, specifically teachers, did not master the advanced techniques of technology, when they had to adopt them in their practices in the classroom in an emergency and immediate way because of the health crisis, which was established with the advance of COVID -19. Very different from distance education, teachers found it almost mandatory to adopt remote teaching practices. It aims to analyze student learning in emergency remote teaching. It relied on the qualitative approach. The possible results will be presented in an authentic way, when evaluating the teaching-learning activities developed during the pandemic, especially in elementary school I, as well as the marks left by the lack of investment in Brazilian education. DOI:https://doi.org/10.56238/Connexpemultidisdevolpfut-152